Application of Elements of Participation in Crime of Trafficking in Goods That are Not in Accordance with Indonesian National Standards - Anggara Wijaya Herman; Iyah Faniyah; Bisma Putra Pratama (Ekasakti Journal of Law and Justice, 2026)
The application of the element of participation by the Directorate of Special Criminal Investigation of the West Sumatra Regional Police against the crime of trafficking in goods that are not in accordance with the Indonesian National Standard (SNI) is to position the qualification as the perpetrator who ordered the act (doen pleger), because the will of the main perpetrator is realized through the actions of other parties under his control. On the other hand, distribution managers, marketing agents, or retailers can be classified as participating in the conduct (medepleger) if they are proven to have knowledge of the non-conformity of goods with applicable standards, but continue with sales activities. Any perpetrator involved in the chain of circulation of goods can be held criminally liable as long as it can be proven that they have knowledge or at least strong suspicion about the non-conformity of the goods with applicable standards. The obstacles encountered by the Directorate of Special Criminal Investigation of the West Sumatra Regional Police in the application of the element of participation to the crime of trafficking in goods that are not in accordance with Indonesian national standards are the most prominent legal obstacles in the investigation of this case are in the aspect of proving the element of guilt and the involvement of the perpetrators which are doctrinally the core of participation. The regulatory structure regarding the crime of trafficking in goods that does not meet standards is still scattered and fragmentative, causing difficulties for investigators in identifying which norms are relevant to ensnare the perpetrators of participation. Non-legal aspects, limited human resource (HR) capacity of investigators are crucial factors that affect the effectiveness of the implementation of inclusion elements, especially in cases involving the distribution of goods digitally. It is related to the low level of legal awareness among business actors and the public, especially in the trade sector of daily necessities.